Evaluating the early impact of AB 617: air pollution, health disparities, and environmental justice in California - Cherry Cheuk Lam Cheung; Adam Eckerd (Environmental Research Communications, 2025)
This study evaluates the initial effectiveness of California’s Assembly Bill 617 (AB 617), enacted to address air pollution impacts in communities designated as environmental justice priorities, a policy approach that has recently been touted as a successful start. These claims of initial success stand in contrast to much of the research on remediation of environmental justice, particularly with respect to air pollution. Despite well-documented disparities in air pollution exposure and its health impacts among racial-ethnic minorities, previous policy efforts to mitigate these effects have had, at best, marginal effects. AB 617 mandates local air districts and the California Air Resources Board (CARB) to reduce air pollution in the most impacted communities by developing monitoring and reduction plans together with affected communities. In this study, we analyzed the PM _2.5 levels and asthma incidence rates in three communities selected to participate in the new program—before and after AB 617 implementation, and compared the results in these selected communities with four other communities nearby. Our findings indicate limited evidence of significant reductions in PM _2.5 levels or asthma incidence rates in the early stages of the post-intervention period. The study discusses potential reasons for the limited impact, including implementation challenges and socio-economic factors, concluding with recommendations for enhancing policy effectiveness in future initiatives.